Highly Porous 3D Printed Tantalum Scaffolds Have Better Biomechanical and Microstructural Properties than Titanium Scaffolds. (28th September 2021) - Fan, Huaquan; Deng, Shu; Tang, Wentao; Muheremu, Aikeremujiang; Wu, Xianzhe; He, Peng; Tan, Caihua; Wang, Guohua; Tang, Jianzhong; Guo, Kaixuan; Yang, Liu; Wang, Fuyou
Abstract : Objective . To test the biomechanical properties of 3D printed tantalum and titanium porous scaffolds. Methods . Four types of tantalum and titanium scaffolds with four alternative pore diameters, #1 (1000-700  μ m), #2 (700-1000  μ m), #3 (500-800  μ m), and #4 (800-500  μ m), were molded by selective laser melting technique, and the scaffolds were tested by scanning electronic microscope, uniaxial-compression tests, and Young's modulus tests; they were compared with same size pig femoral bone scaffolds. Results . Under uniaxial-compression tests, equivalent stress of tantalum scaffold was 411 ± 1.43  MPa, which was significantly larger than the titanium scaffolds (P < 0.05 ). Young's modulus of tantalum scaffold was 2.61 ± 0.02  GPa, which was only half of that of titanium scaffold. The stress-strain curves of tantalum scaffolds were more similar to pig bone scaffolds than titanium scaffolds. Conclusion . 3D printed tantalum scaffolds with varying pore diameters are more similar to actual bone scaffolds compared with titanium scaffolds in biomechanical properties.